O desenvolvimento da criança com Paralisia Cerebral no ambiente familiar - Sofía Rubinstein; Maria Helena da Silva Ramalho; Francisco Camargo Netto (Universidade Federal do Rio Grande do Sul, 2002)
This study looks at the contributions of the family context to the development of the child with Cerebral Palsy in the 5 to 6 year-old age group. The study participants are three families with children who have different kinds of Cerebral Palsy. Semistructured interviews were carried out with the mothers of the children and indirect observations were made through video tape recordings of the activities carried out by the children in the family context. The data obtained answer to the specific goals of this study, which are: a description of the social status of the family; identification and analysis of the activities carried out in the family context, of the interpersonal relationships of the child with Cerebral Palsy, and of the roles performed during the activities in the family context.